Study of Old Relationship of Contraceptive Use of DMPA (Depomedroxy Progesterone Acetate) to Health Problems in Menopause - Tanti Tri Lestary; Ratnanengsih; Grace Pongmekkita (Formosa Journal of Social Sciences (FJSS), 2023)
Depomedroxy Progesterone Acetate is a synthetic progesterone used in the injection method in the Family Planning program. This method is familiarly known as 3-month injection KB in the community. Injecting family planning services can be accessed at Independent Midwives' Practices, Doctor's Practices and Community Health Centers. Based on data for 2021, the most widely used method is injection, which is 33.1% (RI Ministry of Health, 2022). However, using it for a long time, this method will cause a hypoestrogen-like state like menopause. This causes health problems such as decreased libido and increased BMI (Body Mass Index). This research is a qualitative research that uses Chi-Square analysis to assess the relationship between the variables studied. The population in this study were 3-month injection acceptors at PMB Lia Sofa with a sampling technique using Acidental Sampling. This research was conducted from April to July 2022 using a questionnaire as a tool. From this study, it was found that there was a relationship between the duration of 3 months of injection injections with an increase in BMI and a decrease in libido